Comparative Quantitative Study of Acetyl Salicylic Acid in Aspirin Samples Using Spectrophotometry and Volumetric - Khaled Hreeba,; Ezadeen Aboshaloa,; Saleh, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study focuses on the quantification of acetylsalicylic acid (ASA) in aspirin tablets using two analytical approaches: back-titration and spectrophotometric analysis. Significant variations in ASA concentrations were observed across different samples. The back-titration method recorded concentrations ranging from 33.68% to 75.27%, while spectrophotometric analysis yielded values between 26.27% and 74.65%. These discrepancies highlight potential factors such as formulation inconsistencies, manufacturing quality, or chemical interactions during analysis. A comparative evaluation of the two methods reveals that the spectrophotometric method demonstrated higher precision and ease of execution, making it suitable for routine pharmaceutical analysis. However, both methods showed limitations in accuracy. The findings suggest variability in ASA concentrations among different commercial brands, which remain largely within official standards but warrant further investigation to ensure consistency and efficacy. The study underscores the need for refining analytical methods to enhance reliability and calls for improved manufacturing protocols to maintain quality control in pharmaceutical products.